PERBEDAAN HASIL BELAJAR MATEMATIKA SISWA YANG DIAJARKAN MENGGUNAKAN QUANTUM LEARNING TEKNIK MIND MAPPING DENGAN COOPERATIVE LEARNING TEKNIK JIGSAW DI SMP NEGERI 18 TANGERANG - Ahmad Fahrudin (Universitas Pamulang, 2017)
ABSTRACT This study aims to determine there are or not differences math student’s learning outcomes that use Mind Mapping technique Quantum Learning and Cooperative Learning Jigsaw technique. Prior to this study given to the object of study, first conducted test instruments that the validity tests and reliability testing. Before the data analyzed, first tested the requirement that test Lilliefors normality test and homogeneity test by using Fisher's exact test. Based on hypothesis testing using t test obtained t = 5,049 > 1,993 = t(0,05;73. This means H0 reject or accept H1. So, the results of this study concluded that there are differences math student’s learning outcomes that used Mind Mapping technique Quantum Learning and Cooperative Learning Jigsaw technique.